K čemu je antropologizace historie? Několik poznámek ke kontraproduktivní polarizaci poznávacích zájmů v humanitních vědách - Lorenzová, Maren (Dějiny – teorie – kritika, 2024)
This contribution aims to review the axiomatic premises of neurophysiology, psychoanalysis and deconstructionism (in their most extreme forms), and to discuss correspondences and differences in the concepts of humanness on which they are based. This discussion will reveal the high degree of similarity in these underlying concepts. Both sociobiology and psychoanalysis in effect negate human free will to a great extent with their explanations of behaviour as the result of a limited repertoire of basic drives or biochemically regulated patterns. Deconstructionism, on the other hand, while seeming to reject this approach, is in fact ultimatey also grounded in psychoanalytical axioms. On this basis, the value of further pursuing these epistemological paths appears questionable. If work is oriented around recognising the limits of the explainable, in the sense of a classic hermeneutic circle, then it would seem more useful to return to more modest goals, which can only be realised within the context of comprehensive historical and cultural contextualisation. The processes in which human patterns of interpretation and action emerge and are transformed can be reduced neither to "unconscious" drives nor to the autonomous perception of the body by a subject, and nor can they be interpreted as mere de-materialised language.